Determination of Education Funding System, Community Participation and School Principles, on The Quality of Early Children Education in Jambi Province - Bahera, Bahera; Badarussyamsi, Badarussyamsi (International Journal of Advanced Multidisciplinary, 2023)
Talking about the quality of education, it will be directly related to the role of schools as educational institutions. Management of teaching and learning in schools is very meaningful in determining student success. To achieve good school quality, education costs must be managed optimally. Therefore, the stages in education financing management need to be considered. Basically the purpose of education financing management is the implementation of an educational process that is in accordance with the expected learning needs of students. Education financing management in PAUD is in the high category, meaning that school principals in PAUD have been able to carry out education financing management optimally starting from financing planning and budgeting, financing implementation, financing monitoring and control and accountability.